2020
DOI: 10.3390/ijerph17186475
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Dynamic Thermophysical Properties of Clothing and the Walking Speed Input Parameter on the Heat Strain of a Human Body Predicted by the PHS Model

Abstract: The prediction accuracy of the Predicted Heat Strain (PHS) model is affected by the correction approaches of static thermophysical properties of clothing considering the pumping effects of wind and body movement. In this study, a comparison of different correction algorithms for three types of clothing and their influence on the heat strain predicted by the PHS model was carried out with experimental data obtained from the literature. Results show that the dynamic insulation values calculated by ISO 9920 corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…10,11 A few studies have explored applying the PHS model in high thermal insulation clothing ensembles (I cl > 1.5 clo) in high-temperature environments. The results showed that the human body's core temperature wearing firefighters' protective clothing was overestimated by about 1.5 C in exposure to a temperature of 40 C. 12 To this end, the applicability of the correction methods of clothing dynamic thermal insulation in different clothing types has been explored, [13][14][15] including ISO 7933, ISO 9920, and the Lu model. 16 However, the predictive deviation in high insulation clothing ensembles still exceeds the acceptable range (0.2 C).…”
mentioning
confidence: 99%
“…10,11 A few studies have explored applying the PHS model in high thermal insulation clothing ensembles (I cl > 1.5 clo) in high-temperature environments. The results showed that the human body's core temperature wearing firefighters' protective clothing was overestimated by about 1.5 C in exposure to a temperature of 40 C. 12 To this end, the applicability of the correction methods of clothing dynamic thermal insulation in different clothing types has been explored, [13][14][15] including ISO 7933, ISO 9920, and the Lu model. 16 However, the predictive deviation in high insulation clothing ensembles still exceeds the acceptable range (0.2 C).…”
mentioning
confidence: 99%